1985
DOI: 10.1161/01.hyp.7.4.514
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic innervation of cerebral blood vessels decreases in renal hypertensive rats.

Abstract: SUMMARY The ultrastructural distribution of the autonomic nerves of brain arteries was investigated in renal (one-kidney, one clip) hypertensive and normotensive Wistar-Kyoto rats. Sympathetic and nonsympathetic nerve terminals were found only in the adventitial layer of brain arteries of renal hypertensive and normotensive rats. In both normotensive and renal hypertensive rats the total nerve endings were dense in anterior cerebral artery, moderately dense in middle cerebral artery, and sparse in basilar arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…It is interesting to note that GVN increase in all cerebral arteries examined, and AVN decrease or remain unchanged in cerebral arteries of SHR (present study), whereas both GVN and AVN terminals decrease in cerebral arteries of renal hypertensive rats (RHR) (Saito and Lee, 1983). These results suggest that the active neurogenic vasodilation for increasing cerebral blood flow may be weakened or impaired in both RHR and SHR, and the active cerebral vasoconstriction may be improved in SHR but weakened in RHR.…”
Section: Functional Significance Of Cerebral Vessel Innervation In Chsupporting
confidence: 48%
See 1 more Smart Citation
“…It is interesting to note that GVN increase in all cerebral arteries examined, and AVN decrease or remain unchanged in cerebral arteries of SHR (present study), whereas both GVN and AVN terminals decrease in cerebral arteries of renal hypertensive rats (RHR) (Saito and Lee, 1983). These results suggest that the active neurogenic vasodilation for increasing cerebral blood flow may be weakened or impaired in both RHR and SHR, and the active cerebral vasoconstriction may be improved in SHR but weakened in RHR.…”
Section: Functional Significance Of Cerebral Vessel Innervation In Chsupporting
confidence: 48%
“…The increase in GVN terminals in SHR cerebral arteries is probably not due to high blood pressure either. In renal hypertensive rats, both the AVN and GVN terminals per cross-section decrease in the anterior cerebral and basilar arteries (Saito and Lee, 1983). These results suggest that alteration of AVN and GVN in hypertensive animals may be due to factors other than the high blood pressure itself.…”
Section: Is Altered Cerebral Vessel Innervation In Chronic Hypertensimentioning
confidence: 73%
“…This is based on reported results that distribution of cerebral perivascular sympathetic and parasympathetic nerve terminals changes in hypertension (30,31,42). The density of the sympathetic nerve terminals increases in the spontaneously hypertensive rat (SHR) but decreases in the renovascular hypertensive rat (RHR).…”
mentioning
confidence: 99%
“…The physiological significance of this axo-axonal interaction mechanism in the large arteries at the base of the brain is supported by the findings that the axo-axonal interaction mechanismmediated nitrergic vasodilation is diminished in hypertension (Chang et al, 2012). Although the exact reasons underlying this change in hypertension remain to be examined, it has been reported that the parasympathetic nerve terminals significantly decrease while the sympathetic nerve terminals increase or decrease depending on type of hypertension (Lee and Saito, 1984;Saito and Lee, 1985). These morphological alterations in hypertension obviously diminish anatomical basis for the axo-axonal interaction leading to decreased neurogenic nitrergic vasodilation in hypertension (Lee and Saito, 1984;Saito and Lee, 1985;Chang et al, 2012).…”
Section: Introductionmentioning
confidence: 91%
“…Although the exact reasons underlying this change in hypertension remain to be examined, it has been reported that the parasympathetic nerve terminals significantly decrease while the sympathetic nerve terminals increase or decrease depending on type of hypertension (Lee and Saito, 1984;Saito and Lee, 1985). These morphological alterations in hypertension obviously diminish anatomical basis for the axo-axonal interaction leading to decreased neurogenic nitrergic vasodilation in hypertension (Lee and Saito, 1984;Saito and Lee, 1985;Chang et al, 2012). Accordingly, the axo-axonal interaction mechanism-mediated neurogenic vasodilation may play an important role, especially, as a protective mechanism in increasing brainstem blood flow to meet the O 2 demand when facing an acutely stressful situation (Chang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%